Innovation of Islamic Financial Products and Services in the Digital - Cindi Safitri; Anggun Okta Fitri (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2025)
The advancement of digital technology has led to significant changes in various areas of the industry, including Islamic banking. The digital Era has created new opportunities for Islamic banking to innovate in developing products and services that are more accessible, efficient, and in accordance with Islamic principles. This research uses qualitative method with literature study approach. Library sources can be obtained from books, journals, magazines, research results (theses and dissertations), and other relevant sources (internet, newspapers, and others). The results show that innovation of products and services related to Islamic finance in the digital era has significant potential to improve financial accessibility, improve operational efficiency, increase transparency, develop products and services that are more in line with the needs of Micro, Small, Medium and large enterprises, and increase awareness of financial products. This paper provides guidance on how to improve the innovation of Islamic banking products and services in the digital era, such as improving more personalized products and services, improving standards of financial literacy and education.